Development of GC-MS based cytochrome P450 assay for the investigation of multi-herb interaction - Oh, Hyun-A; Lee, Hyunbeom; Kim, Donghak; Jung, Byung Hwa (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2017)
As drug interactions with cytochrome P450 enzymes become increasingly important in the field of drug discovery, a high-throughput screening method for analysing the effects of a drug is needed. We have developed a simple and rapid simultaneous analytical method using a cocktail approach for measuring the activities of seven cytochrome P450 enzymes (CYP1A2, CYP2A6, CYP2C9, CYP2C19, CYP2D6, CYP2E1 and CYP3A4). Human liver microsomes were used as a source for the seven cytochrome P450 enzymes, and a gas chromatography-mass spectrometry (GC-MS) was used for analysing their activities. Kinetic studies and inhibition assays of CYP enzymes were performed using known substrates and inhibitors for validating and comparing the reaction rates and time-dependent activities between methods using each substrate versus a method using a cocktail solution. The optimized cocktail method was successfully applied to evaluate the effects of the decoction of Socheongryong-tang (SCRT) on cytochrome P450 enzymes. Our cocktail method provides a simultaneous high-throughput activity assay using GC-MS for the first time. This method is applicable for analysing the drug interactions of various plant-derived mixtures. (C) 2016 Elsevier Inc. All rights reserved.
Keywords: HUMAN LIVER-MICROSOMES; IN-VITRO; MASS-SPECTROMETRY; DRUG-INTERACTION; LIQUID-CHROMATOGRAPHY; COCKTAIL APPROACH; INHIBITION ASSAY; CYP450 ENZYMES; LC-MS/MS; MEDICINE